High‐Valent Iron‐Oxo and ‐Nitrido Complexes: Bonding and Reactivity. Issue 9 (19th July 2016) - Mondal, Bhaskar; Roy, Lisa; Neese, Frank; Ye, Shengfa
Abstract: Multiple‐bonded iron‐oxo and ‐nitrido species have been identified or proposed as key intermediates in a range of important chemical transformations. The reported model complexes feature various coordination geometries and distinct electronic structures, and therefore exhibit diverse reactivity. The present contribution highlights the synergy from both experimental and theoretical standpoints to elucidate their different bonding situations and delineate their common mechanistic features in hydrogen‐atom abstraction processes. Our analysis reveals that a radical centered on the abstracting atom E (E=O, N), which is generated via homolysis of covalent Fe−E bonds upon approaching the transition state, is an intrinsic C−H cleaving agent. The iron‐oxo species is predicted to be more reactive than its nitride congener, in general, because the O−H bond formed in the H‐atom transfer process is often stronger than the corresponding N−H bond. Abstract :